Does language proficiency modulate oculomotor control? Evidence from Hindi–English bilinguals - SINGH, NIHARIKA; MISHRA, RAMESH KUMAR (Bilingualism (Cambridge, England), 2012)
Though many previous studies have reported enhanced cognitive control in bilinguals, few have investigated if such control is modulated by language proficiency. Here, we examined the inhibitory control of high and low proficient Hindi–English bilinguals on an oculomotor Stroop task. Subjects were asked to make a saccade as fast as possible towards the appropriate colour patch among competitors and distractors suppressing an eye movement evoked by the meaning of the word. High proficient bilinguals quickly oriented their attention towards the correct colour patch while effectively controlling the Stroop interference compared with low proficient subjects, on both colour and direction words. High proficient bilinguals also had fewer saccadic errors and demonstrated overall faster saccadic latency on all trial types. The results provide strong evidence for enhanced oculomotor control in proficient bilinguals compared with the less proficient ones.